IDENTIFICATION SERVICE SYSTEM UNLOADING FISHING BOATS IN THE OCEAN FISHING PORT BELAWAN - Veronika Sitanggang; Alit Hindri Yani; Syaifuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in 17-31 March 2015 in the ocean fishing portBelawan. This research aims to identify the service system unloading fishing botsas well as facilities and equipment to support the smooth operation of loading andunloading of vessel fishing in the ocean fishing port Belawan. The study wasconducted using a survey method. To solve the problem of the unloading serves inthe ocean fishing port Belawan was divided into two stages. First stage was toevaluate the existing capasity of an unloading port. Second stage was to find outof the optimum number of server that should be provided this time and to forcastof the server need in the next five year or in 2018. Data were quantitativelyanalysed by using queuing model and then combined with the total of minimumcost to find out the optimum number of server. The results showed that theoptimum number of the server for an average of ship arrival from january todecember 2014 was 10 servers, while in the lowest and peak season about 3 and15 servers were needed. Furthermore, the forecasting of ship arrival number in2018 showed that there would be about 9.244 ships arriving at PPS Belawan andthe arrival rate of ship per day was 25,33 so it would be about 12 servers.Kata kunci: Optimize, Unloading, Queuing, Server